No-till with plastic film mulching combined with N fertilizer reduction improves water productivity of spring wheat - Falong Hu; Qiang Chai; Yan Tan; Cai Zhao; Aizhong Yu; Zhilong Fan; Wen Yin; Hong Fan; Wei He (Farming System, 2023)
Meeting the challenge of achieving high yields with less water utilization has raised concerns regarding developing water-saving agricultural practices. Conservation tillage and N fertilization are promising and widely used to improve water use efficiency; however, the mechanisms underlying still need to be addressed. Field experiments were conducted at the Hexi Corridor of northwestern China from 2019 to 2020, where tillage practices, i.e., conventional tillage (CT) and no-till with plastic film mulching (NTP), and N fertilizer rates (135 ​kg ​N ha−1 [N135], 180 ​kg ​N ha−1 [N180], and 225 ​kg ​N ha−1 [N225]) were applied. The results showed that NTP led to a soil water change (i.e., water consumption from the soil) increased by 101.7% during the concurrent growth period in a specific soil layer at 0–30 ​cm compared to CT. It also lowered the total soil evaporation (22.3%) and improved the total transpiration (13.4%). Consequently, no significant difference in evapotranspiration between the NTP and CT groups was observed. N135 decreased the soil water change by 9.0% and 15.2%, and improved the total soil evaporation by 3.4% and 8.4%, respectively, compared with N180 and N225. Tillage practices and N fertilization had an interactive effect on water productivity. Under CT, the grain yield and water use efficiency based on evapotranspiration (WUEET) of N180 were reduced by 9.4% and 7.6%, respectively, compared to those of N225. In contrast, under NTP, no significant difference was found. Structural equation modeling (SEM) analysis showed that the tillage practices improved WUEET by reducing soil evaporation and improving transpiration. However, N fertilization improved WUEET uniquely by improving transpiration. Consequently, we concluded that no-till combined with 180 ​kg ​N ha−1 could be used as an effective measure to achieve higher water productivity of spring wheat in arid areas.